Bordetella bronchiseptica Bcr4 antagonizes the negative regulatory function of BspR via its role in type III secretion. (14th December 2018) - Nishimura, Ryutaro; Abe, Akio; Sakuma, Yusuke; Kuwae, Asaomi
ABSTRACT: Bordetella species, including B. pertussis, have a type III secretion system that is highly conserved among gram‐negative pathogenic bacteria. Genes encoding the component proteins of the type III secretion system are localized at the bsc locus in the Bordetella genome. Here, the function of a hypothetical protein Bcr4 encoded at the bsc locus in the B. bronchiseptica genome was investigated. A Bcr4‐deficient mutant was created and the amounts of type III secreted proteins (e.g., BopB, BopN and Bsp22) in both the supernatant fraction and whole‐cell lysates of the Bcr4‐deficient mutant were determined. It was found that the amounts of these proteins were significantly lower than in the wild‐type strain. The amounts of type III secreted proteins in the supernatant fraction and whole‐cell lysates were much greater in a Bcr4‐overproducing strain than in the wild‐type strain. The type III secreted protein BspR reportedly negatively regulates the type III secretion system. Here, it was observed that a Bcr4 + BspR double‐knockout mutant did not secrete type III secreted proteins, whereas the amounts of these proteins in whole‐cell lysates of this mutant were nearly equal to those in whole‐cell lysates of the BspR‐deficient mutant. Bcr4 thus appears to play an essential role in the extracellular secretion of type III secreted proteins. Our data also suggest that Bcr4 antagonizes the negative regulatory function of BspR.